IDNLearn.com: Where your questions meet expert advice and community insights. Join our interactive Q&A platform to receive prompt and accurate responses from experienced professionals in various fields.
Sagot :
Certainly! Let's start by analyzing the given expression [tex]\( 4^7 \div 4^9 \)[/tex].
### Step 1: Simplify the Expression Using Properties of Exponents
We can use the property of exponents that states [tex]\( \frac{a^m}{a^n} = a^{m-n} \)[/tex]. Here, [tex]\( a = 4 \)[/tex], [tex]\( m = 7 \)[/tex], and [tex]\( n = 9 \)[/tex].
So,
[tex]\[ 4^7 \div 4^9 = \frac{4^7}{4^9} \][/tex]
Applying the exponent rule:
[tex]\[ \frac{4^7}{4^9} = 4^{7-9} \][/tex]
Simplify the exponent:
[tex]\[ 7 - 9 = -2 \][/tex]
Thus,
[tex]\[ \frac{4^7}{4^9} = 4^{-2} \][/tex]
### Step 2: Interpret the Negative Exponent
By definition, a negative exponent represents the reciprocal of the base raised to the positive version of the exponent. In this case:
[tex]\[ 4^{-2} = \frac{1}{4^2} \][/tex]
Let's break this down to show the steps explicitly:
1. The negative exponent [tex]\(-2\)[/tex] indicates that we need to take the reciprocal of [tex]\(4^2\)[/tex].
2. Calculate [tex]\(4^2\)[/tex]:
[tex]\[ 4^2 = 4 \times 4 = 16 \][/tex]
3. Now, take the reciprocal:
[tex]\[ \frac{1}{4^2} = \frac{1}{16} \][/tex]
### Step 3: Final Verification
Now, let's verify that our interpretation holds true for the values:
First, calculate [tex]\(4^{-2} \)[/tex]:
[tex]\[ 4^{-2} = \frac{1}{4^2} \][/tex]
We already know that:
[tex]\[ 4^2 = 16 \][/tex]
So,
[tex]\[ \frac{1}{4^2} = \frac{1}{16} \][/tex]
Therefore, the value of [tex]\( 4^{-2} \)[/tex] is indeed:
[tex]\[ 4^{-2} = \frac{1}{16} \][/tex]
### Conclusion
Hence, we have shown that:
[tex]\[ 4^7 \div 4^9 = 4^{-2} \][/tex]
and that
[tex]\[ 4^{-2} = \frac{1}{4^2} \][/tex]
Everything checks out mathematically. This illustrates the property of negative exponents and their relationship to reciprocals effectively.
### Step 1: Simplify the Expression Using Properties of Exponents
We can use the property of exponents that states [tex]\( \frac{a^m}{a^n} = a^{m-n} \)[/tex]. Here, [tex]\( a = 4 \)[/tex], [tex]\( m = 7 \)[/tex], and [tex]\( n = 9 \)[/tex].
So,
[tex]\[ 4^7 \div 4^9 = \frac{4^7}{4^9} \][/tex]
Applying the exponent rule:
[tex]\[ \frac{4^7}{4^9} = 4^{7-9} \][/tex]
Simplify the exponent:
[tex]\[ 7 - 9 = -2 \][/tex]
Thus,
[tex]\[ \frac{4^7}{4^9} = 4^{-2} \][/tex]
### Step 2: Interpret the Negative Exponent
By definition, a negative exponent represents the reciprocal of the base raised to the positive version of the exponent. In this case:
[tex]\[ 4^{-2} = \frac{1}{4^2} \][/tex]
Let's break this down to show the steps explicitly:
1. The negative exponent [tex]\(-2\)[/tex] indicates that we need to take the reciprocal of [tex]\(4^2\)[/tex].
2. Calculate [tex]\(4^2\)[/tex]:
[tex]\[ 4^2 = 4 \times 4 = 16 \][/tex]
3. Now, take the reciprocal:
[tex]\[ \frac{1}{4^2} = \frac{1}{16} \][/tex]
### Step 3: Final Verification
Now, let's verify that our interpretation holds true for the values:
First, calculate [tex]\(4^{-2} \)[/tex]:
[tex]\[ 4^{-2} = \frac{1}{4^2} \][/tex]
We already know that:
[tex]\[ 4^2 = 16 \][/tex]
So,
[tex]\[ \frac{1}{4^2} = \frac{1}{16} \][/tex]
Therefore, the value of [tex]\( 4^{-2} \)[/tex] is indeed:
[tex]\[ 4^{-2} = \frac{1}{16} \][/tex]
### Conclusion
Hence, we have shown that:
[tex]\[ 4^7 \div 4^9 = 4^{-2} \][/tex]
and that
[tex]\[ 4^{-2} = \frac{1}{4^2} \][/tex]
Everything checks out mathematically. This illustrates the property of negative exponents and their relationship to reciprocals effectively.
Thank you for joining our conversation. Don't hesitate to return anytime to find answers to your questions. Let's continue sharing knowledge and experiences! IDNLearn.com has the solutions you’re looking for. Thanks for visiting, and see you next time for more reliable information.